PENDOKUMENTASIAN STANDAR ASUHAN KEPERAWATAN DI RUMAH SAKIT UMUM DAERAH MAMUJU - Supratti Supratti; Ashriady Ashriady (Jurnal Kesehatan Manarang, 2016)
Services in Regional Hospital of Mamuju generally still complained of patients and their families in all treatments. The aim of research to determine the standard of nursing care documentation in Regioanal Hospital of Mamuju. This type of research is descriptive quantitative research with observational approach. This study was conducted in March to Okober 2015 in Regional Hospital of Mamuju. Subjects in this research is all nurses who perform nursing documentation with a number of research subjects as many as 93 people. Variables studied nursing assessment, diagnosis, planning, implementation and evaluation using a standard observation sheet nursing care, used univariate data analysis. The results showed nursing documentation based on the standard of nursing care which is less complete assessment category 91 nurses (97.8%), nursing diagnoses relevant category 47 nurses (50.5%), planning the relevant category 44 nurses (47.3%), the implementation of category complete 49 nurses (52.7%) and the evaluation of the complete category 59 nurses (63.4%).